Enhancement of Tomato Growth Through Rhizobacteria and Biocontrol of Associated Diseases - Hasna El hjouji; Redouan Qessaoui; Salahddine Chafiki; El Hassan Mayad; Hafsa Houmairi; Khadija Dari; Bouchaib Bencharki; Hinde Aassila (Life)
The purpose of this study was to investigate the growth-promoting effects of four rhizobacterial isolates (RS60, RS65, RS46, and RP6) isolated from the tomato rhizosphere. These isolates were screened for key plant growth-promoting rhizobacteria (PGPR) mechanisms, including ammonia production, nitrogen fixation, phosphate solubilization, indole-3-acetic acid (IAA) production, and siderophore synthesis. Their potential to enhance seed germination and tomato plant growth was investigated in controlled and greenhouse conditions. Four isolates exhibited multiple PGPR attributes, notably IAA and ammonia production as well as phosphate solubilization. The results revealed that these strains significantly enhanced tomato seed germination and shoot growth in vitro, with RS65 showing the highest germination rate (70%). However, no significant differences in early seedling responses were observed under greenhouse conditions when compared to the control. Thirty days after inoculation, greenhouse results revealed that the four studied strains significantly increased growth metrics including shoot length, number of leaves, collar diameter, and dry weight. The isolate RP6 showed a significant effect on the growth of the plant, with an average shoot length of 34.40 cm and nine leaves per plant. In vitro antagonism assays demonstrated that isolates RS60, RS65, and RP6 effectively inhibited the growth of Botrytis cinerea, Alternaria alternata, and Oidium lycopersici, with inhibition rates exceeding 65%. These antagonistic activities were linked to the production of hydrolytic enzymes (chitinase, cellulase, pectinase, protease), siderophores, and hydrogen cyanide (HCN). Molecular identification through 16S rRNA gene sequencing confirmed the isolates as Bacillus cereus (RS60), Bacillus pumilus (RS46), Bacillus amyloliquefaciens (RP6), and Bacillus velezensis (RS65), each showing over 97% sequence similarity with reference strains. These findings underscore the potential of the selected Bacillus spp. as promising biofertilizers and biocontrol agents for sustainable tomato cultivation and support their inclusion in integrated disease and nutrient management strategies.